PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PELAYANAN SATUAN KERJA DENGAN KOMITMEN ORGANISASIONAL DAN KOMPETENSI SEBAGAI VARIABEL INTERVENING PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) PONTIANAK - B2041141009, DANANG TRI SURYANTO (Equator Journal of Management and Entrepreneurship (EJME), 2018)
The establishment of government agency is primarily based on their uppermost mission which is to provide service to public. In every government agencies, their function and assignment are affected by certain procedure and policy as the attempt to fulfill society’s needs in terms of quality and quantity. The final goal of this action is to give the best service to anyone who use the service itself. In accomplishing the mission, it is known that each government institution is affected by the attitude and behavior of the surrounding society. Besides that, the possibility to accomplish the mission is also affected by employees’ capability and effortsin executing each work unit in the department.  The aim of this research study is to identifythe influence of organizational culture, organizational commitment and competence as intervening variable in Pontianak Treasury Office. The study involved 60 employees of Pontianak Treasury Office. The method used in this research is by using the multiple linear regression analysis with the use of Statistical Package for Social Sciences (SPSSS 21.0 for windows). This research also uses validity check, reliability check, normality test, linearity test and path analysis. The result of this research showed that the organizational culture has a positive effect on the performance of work unit services, organizational culture has significant positive effect on organizational commitment. Organizational commitment has significant positive effect on employee performance, organizational culture has a significant and positive effect on organizational competence and organizational competence has a positive effect on the employees’ performance. Key word : Organizational Culture, Organizational Commitment, Competence and Performance Job Satisfaction, Organizational Citizenship Behavior and Performance